HUBUNGAN DUKUNGAN SOSIAL DENGAN MEKANISME KOPING INDIVIDU PADA PENYANDANG DIABETES MELITUS TIPE 2 DI PUSKESMAS GUNUNGPATI - Imam Bachtiar; Ismonah; Hartoyo, Mugi (Persatuan Perawat Nasional Indonesia (PPNI) Jawa Tengah, 2023)
Diabetes Mellitus is a disease indicated by high blood glucose. This disease is a chronic disease that an individual suffers in his or her life. The psychological changes, such as stress suffered by Diabetes Mellitus type-2 patients could influence their blood glucose content instability. Thus, the patients require adaptive coping mechanisms to manage and adapt the stress. One of the influential factors of individual coping mechanisms is social support from family, friends, and significant other. This research examined the correlation between social support and individual coping mechanism of diabetes mellitus type-2 patients. This cross-sectional research applied consecutive sampling on 63 respondents suffering from diabetes mellitus type 2 in Gunungpati health care center. The researchers took the data with the Multidimensional Scale of Perceived Social Support (MSPSS) and Cope Inventory. The Pearson Product Moment obtained a p-value of 0.000 (< 0.05) with an r-value of 0.430, indicating a significant, strong, and positive correlation between social support with individual coping mechanisms in diabetes mellitus type-2 patients. This result suggested high social support led to high individual adaptive coping mechanisms. The researchers recommended nurses educate the families, friends, and close friends of diabetes mellitus type-2 patients so they could provide social support. This effort could realize adaptive coping mechanisms